Optic disk protrusion on transocular ultrasonography is a new finding seen in patients with intracranial hypertension. Issue 1 (31st October 2019) - Terasawa, Yuka; Arai, Ayumi; Sakai, Kenichiro; Mitsumura, Hidetaka; Iguchi, Yasuyuki
Abstract: We report a case with intracranial hypertension having new transocular ultrasonography finding. A forty‐five years old female with a long‐lasting headache and visual field abnormality was admitted to our hospital. She had bilateral papilloedema. After several examinations, she was diagnosed as idiopathic intracranial hypertension. She was examined with transocular ultrasonography to measure optic nerve sheaths diameter (ONSD). ONSD was 6.0mm on right side and 7.5mm on left side, and a new finding "optic disk protrusion" (ODP) was discovered. Three months after starting medication, her symptoms got better and her optic edema disappeared. She was re‐examined with transocular ultrasonography found the "ODP" had also disappeared. ODP would be simple finding to detect intracranial hypertension.